2011
DOI: 10.1186/1478-4505-9-s1-s6
|View full text |Cite
|
Sign up to set email alerts
|

National policy development for cotrimoxazole prophylaxis in Malawi, Uganda and Zambia: the relationship between Context, Evidence and Links

Abstract: BackgroundSeveral frameworks have been constructed to analyse the factors which influence and shape the uptake of evidence into policy processes in resource poor settings, yet empirical analyses of health policy making in these settings are relatively rare. National policy making for cotrimoxazole (trimethoprim-sulfamethoxazole) preventive therapy in developing countries offers a pertinent case for the application of a policy analysis lens. The provision of cotrimoxazole as a prophylaxis is an inexpensive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 29 publications
(39 reference statements)
5
45
0
Order By: Relevance
“…Our findings suggest that context forms an important set of influences on evidence-informed health policy development, which is consistent with other similar studies (Dobrow et al, 2006;Hutchinson, 2011;Hutchinson et al, 2011;Mirzoev et al, 2013). Although most influences reported by our respondents appear to be facilitators, we also found that similar factors can both strengthen or undermine the role of evidence: for example, availability of resources can facilitate generation of evidence, whereas resource constraints were referred to as a barrier thus limiting communication of evidence in both Nigeria and India.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings suggest that context forms an important set of influences on evidence-informed health policy development, which is consistent with other similar studies (Dobrow et al, 2006;Hutchinson, 2011;Hutchinson et al, 2011;Mirzoev et al, 2013). Although most influences reported by our respondents appear to be facilitators, we also found that similar factors can both strengthen or undermine the role of evidence: for example, availability of resources can facilitate generation of evidence, whereas resource constraints were referred to as a barrier thus limiting communication of evidence in both Nigeria and India.…”
Section: Discussionsupporting
confidence: 81%
“…Final manuscript (NOT anonymised) development in different countries (de Savigny et al, 2012;Hutchinson et al, 2011;Ricketts, 2010), despite a growing interest in improving the understanding of facilitators and constraints to evidence-informed health policymaking in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The role would include raising awareness of decision makers to important fi ndings and bringing stakeholders together to begin the decision-making process. For example, after the national policy development on co-trimoxazole prophylaxis for HIV-positive individuals in Malawi, Uganda, and Zambia, 16 a policy entrepreneur was used in Malawi to help bridge the gap between operational research and policy networks. In Malawi, research evidence was swiftly translated into policy and practice, 53 whereas in the other two countries this translation was slow.…”
Section: Translation Of Research Results Into Actionmentioning
confidence: 99%
“…11 Similar examples of engagement of stakeholders at the outset of research include a study showing the benefi ts of co-trimoxazole prophylaxis for people with HIV and another noting the negative eff ect of user fees on patients' outcomes in HIV programmes. [15][16][17] The key message from these experiences is that, at the outset, the most important people needed to support and implement the study fi ndings should be identifi ed and engaged.…”
Section: Why Operational Research Might Fail To Aff Ect Policy and Prmentioning
confidence: 99%
“…45 Recent findings also indicate that results from local operational research on cotrimoxazole preventive therapy for HIV were put into national policy in Malawi and Uganda faster than the results of randomized-controlled trials testing the same therapy in Zambia. 46 Thus, health policy and systems research improves health care by, first, generating evidence informed by local constraints on the best delivery methods for interventions and then linking this evidence to changes in treatment practice and policy. 13 Ultimately, research on product development and on health policy and systems are complementary.…”
Section: Impact Of Imbalancementioning
confidence: 99%